A Review on COVID-19 Outbreak Marketing and Corporate Social Responsibility (CSR) - Rudresh S; Manu Vasudevan Unni (International Journal of Engineering and Management Research, 2022)
The research paper focuses on the evidence-based on a preliminary study conducted on how the COVID-19 outbreak might affect the evolution of business obligations to discharge the activities which could uplift society and marketing. Ironically, it is true that the pandemic has provided an excellent opportunity for corporations to redirect their focus points and to comprehend the newer dimension of customers’ ethical decision-making process. This outbreak has a significant impact on marketing and magnifies the approach towards the strategic marketing efforts drawn by firms as opposed to content marketing. We conclude the study by outlining a number of research issues and areas that have the potential to be productive.